Nazwy ustroju społecznego i władców w polskich XVI-wiecznych przekładach Ewangelii = Names of social systems and names of rulers in Polish 16th century translations of the Gospels - Kępińska, Alina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of paper is to present names of social systems and names of rulers in the four Gospels. The lexis was selected from ten Polish translations of the Gospels, contained in the online edition of "Szesnastowieczne przekłady Ewangelii" [Sixteenth-Century Translations of the Gospels] edited by Izabela Winiarska-Gorska. In this article are exemplified of native words such as "królestwo", "książę", "król", "królowa" and borrowings such as "tetrarcha".
Keywords: polskie XVI-wieczne tłumaczenia Ewangelii; nazwy ustroju społecznego; nazwy władców; Polish 16th century translations of the Gospels; names of social systems; names ofrulers